Precise and convenient size barcode on microfluidic chip for multiplex biomarker detection. Issue 19 (31st August 2021) - Tang, Man; Chen, Jinyao; Lei, Jia; Ai, Zhao; Liu, Feng; Hong, Shao-Li; Liu, Kan
Abstract : A size barcode method is presented based on a wedge-shaped microfluidic chip. This method is simple, precise, and capable of simultaneous detection multiplex biomarkers, demonstrating significant potential in point-of-care tests. Abstract : The existing multiplex biomarker detection methods are limited by the high demand for coding material and expensive detection equipment. This paper proposes a convenient and precise coding method based on a wedge-shaped microfluidic chip, which can be further applied in multiplex biomarker detection. The proposed microfluidic chip has a microchannel with continuously varying height, which can naturally separate and code microparticles of different sizes. Our data indicate that this method can be applied to code more than 5 or 7 kinds of microparticles, even when their size discrepancies are smaller than 1 μm. Based on these, multiplex biomarker detection can be implemented by using microparticles of different sizes, hence each kind of microparticle that coats one kind of antibody represents the species of targets. This method is simple and easy to operate, with no clogging or sophisticated coding design, showing its significant potential in the area of point-of-care tests (POCT).